The Effect of Fuel Adjustment Clauses on the Systematic Risk and Market Values of Electric Utilities: Discussion - Marshall, William (Journal of Finance, 1980)
William Marshall, The Effect of Fuel Adjustment Clauses on the Systematic Risk and Market Values of Electric Utilities: Discussion, The Journal of Finance, Vol. 35, No. 2, Papers and Proceedings Thirty-Eighth Annual Meeting American Finance Association, Atlanta, Georgia, December 28-30, 1979 (May, 1980), pp. 385-387